Perceived COVID-19 crisis strength and teachers’ emotional labor: mediating role of interpersonal stress and moderating role of gender - Shi, Yantao; Hu, Qingle; Tao, Qinghuan (Frontiers in Psychology, 2024)
Perceived COVID-19 crisis strength has been associated with teachers' emotional labor, but little is known about the mediating and moderating mechanisms underlying this association. This study aimed to explore whether interpersonal stress would mediate the relationship between perceived COVID-19 crisis strength and emotional labor, and whether gender would moderate the indirect pathway between perceived COVID-19 crisis strength and interpersonal stress.Participants were 889 primary-and secondary-school teachers from Guangxi, China, selected using convenient sampling method. They completed measurements regarding emotional labor, interpersonal stress, and perceived COVID-19 crisis strength. Results showed that perceived COVID-19 crisis strength was negatively associated with deep acting but not surface acting, and this association was fully mediated by interpersonal stress. Moreover, the indirect relationship between perceived COVID-19 crisis strength and interpersonal stress was moderated by gender, with the indirect relationship being stronger for male teachers than for female teachers. This study illuminates the psychological mechanisms underlying the association between perceived COVID-19 crisis strength and emotional labor, enriching our understanding of this association and gender differences among primary and secondary school teachers.